Measurement of Agricultural Supply Chain Performance: A Sysematic Literature Review - Adistya, Adilla; Oksalia, Elvira Putri; Kemala, Nida (Jurnal MeA (Media Agribisnis), 2024)
This research aims to describe supply chain performance measurements and performance matrices, which are performance assessment points, and identify the causes of high and low supply chain performance scores and the impact of supply chain quality on economic sustainability. This research takes the form of a systematic literature review consisting of various selected Scopus-indexed international journals, selected based on journal content that is relevant to the topic discussed in the research. Most of the previous articles only focused on supply chain optics in general. Hence, the results of this research are in the form of an explanation of supply chain performance issues using the BSC, SCOR, AHP, and DEA methods, as well as a description of the supply chain performance matrix in assessing supply chain performance. – Due to the research approach chosen, this research may lack specificity due to the large number of articles sampled. Therefore, researchers are encouraged to carry out further documentation refinement. This article includes implications for measuring supply chain performance by the company's managerial needs as well as for research that adapts to the form of the company.